Performance Evaluation Of A Motorized Potato (Ipomoea Batata L.) Peeling Machine - Adedipe Jide Olusegun; Adepoju Y.A; Yusuf I.O; Oyeleke O.S (METALOGRAM, 2025)
This study evaluates the performance of a simple motorized potato (Ipomoea batatas L.) peeling machine. Evaluation parameters include peeling efficiency, weight loss, machine speed, and capacity. It highlights the correlations and variations between these parameters using graphical illustrations. The materials used were categorized into component materials, measuring tools and potato samples. Peeling operation was carried out and replicated 20 times. Results revealed an average weight loss of 27.5g, suggesting a well-calibrated blade engagement, a mean speed of 3.1 potatoes min, an average throughput of 450g/min and an average efficiency of 86.16%. There was a strong positive linear relationship between the initial weight and the final weight which infers a uniform peeling across all sizes. There was no consistent correlation between weight loss and throughput; this suggests that throughput was not tied to peeling aggressiveness, allowing focus on waste minimization without compromising output. Result revealed that as speed increases, throughput also increases, implying that speed was a productivity driver. There was an inverse relationship between weight loss and efficiency; high losses could signal over-aggressiveness. Efficiency was fairly high across all speeds ranging between 84.44 – 87.88 %, but tends slightly dip at the highest speeds. This suggests that increasing can slightly reduce peeling accuracy. In conclusion, the machine reveals a robust yet improvable machine for potato peeling. We therefore recommended that a sorter, speed controller and a feedback sensor be attached for optimization.